I Don't Feel Noways Tired: Why Black Teachers Will Persevere through the Anti-Truth Movement - Duncan, Kristen E.; Chisholm, Alex E.; Lewis, Terrance J. (Critical Education, 2025)
The current anti-truth context, in which discussions of race and racism in K-12 schools are rendered illegal, is just the latest iteration of anti-Black legislation that impacts schools. In this article, we historicize the contemporary moment by using BlackCrit and fugitive pedagogies to discuss how Black teachers have navigated discussions of race and racism with Black students through previous anti-Black contexts, noting that we believe contemporary Black teachers will continue in this rich tradition, despite current legislation.